CONVERGENCE OF TRADITIONAL CORPORATE GOVERNANCE AND MODERN CORPORATE GOVERNANCE REFORMS: IS KING II déja vu FOR BOARDS OF DIRECTORS OR IS IT A SET OF NEW PRINCIPLES? - Tshepo Mongalo (Obiter, 2023)
Contrary to popular belief, corporate governance is not a new subject. In fact, corporate governance has been practised for as long as there have been corporate entities. Corporate governance has always been reflected in legislation such as the Companies Act, Insolvency Act, Insider Trading Act and similar legislation. However, some of the recent recommendations resulting from reforms in this area reflect the improvement of corporate governance standards. This article is an attempt to point out similarities and divergences between traditional corporate governance and modern corporate governance as suggested by the latest reforms, particularly in the King Report on corporate governance (2002).